Kongish translanguaging and the commodification of an urban dialect - Lee, Tong-King ca. 20./21. Jh (Cambridge elements, 2023)
This Element introduces Kongish as a translingual and multimodal urban dialect emerging in Hong Kong in recent years and still in the making. Through the lens of translanguaging and linguistic commodification, and using the popular Facebook page Kongish Daily as a case in point, the study outlines the semiotic profile of Kongish. It examines how Kongish communications draw on a full range of performative resources, thriving on social media affordances and a creative-critical ethos. The study then turns to look at how Kongish is commoditized in a marketing context in the form of playful epithets emplaced on locally designed products, demonstrating how the urban dialect is not merely a niche medium of communication on social media, but has become integral to commercial, profit-driven practices. The Element concludes by challenging the proposition that Kongish must be considered a 'variety' of English, arguing instead that it is an innominate term embodying translanguaging-in-action